Correlation of intestinal bacteria, fungi and dietary nutrient intake in NAFLD patients with spleen deficiency syndrome - Lin, Guiru; Ou, Wanyi; Yang, Jianmei; Chen, Dongliang; Wang, Yuanfei; Wu, Aiping; Gao, Lilian; Qu, Wan; Lin, Chenli; Liang, Yinji (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundSpleen deficiency syndrome (SDS) is one of the primary Traditional Chinese Medicine (TCM) syndromes in Non-alcoholic fatty liver disease (NAFLD). Diet influences NAFLD and SDS through the intestinal microbiota. The current study aimed to investigate the interrelationships of intestinal bacteria, fungi and dietary nutrient intake in NAFLD patients with SDS.MethodsThe NAFLD TCM Patient Reported Outcome (PRO) Scale was administered to evaluate the TCM clinical symptoms of NAFLD patients. The Spleen Deficiency PRO Scale and Food Frequency Questionnaire (FFQ) were employed to respectively diagnose spleen deficiency syndrome and assess dietary nutrient intake, energy-adjusted dietary inflammatory index (E-DII), and dietary diversity scores (DDS) in NAFLD patients. Subsequently, stool samples were collected for 16S rRNA gene and ITS2 region sequencing to analyze the interrelationships among target intestinal bacteria, fungi, and dietary nutrient intake.ResultsThe NAFLD TCM PRO Scale indicated that the average score for symptoms related to SDS in NAFLD patients was 4.13 ± 0.40. Compared with NAFLD patients without SDS, those with SDS had insufficient dietary nutrient intake of diet-derived antioxidants such as carotene and folic acid, stronger pro-inflammatory effects of food, and reduced dietary diversity (P < 0.05). Additionally, sufficient dietary diversity was identified as a protective factor against SDS in NAFLD (OR: 0.424; 95% CI: 0.309, 0.583; P < 0.001). 16S rRNA gene and ITS2 region sequencing results showed that Collinsella (LDA = 3.947, P = 0.046) and Rhizopus (LDA = 3.196, P = 0.01) were enriched in NAFLD patients with SDS, whereas Intestinimonas was markedly increased in NAFLD patients without SDS (LDA = 2.015, P = 0.02). Correlation analysis demonstrated that Gemmiger and Rhizopus were significantly positively correlated (r = 0.778, P < 0.001), as were Candida and Segatella (r = 0.569, P < 0.001). Intestinimonas was positively correlated with the intake of antioxidant and anti-inflammatory nutrients such as dietary fiber, vitamin C, and iron (0.2 < r < 0.5, P < 0.05), while niacin intake was negatively correlated with Rhizopus abundance (r = -0.39, P = 0.025).ConclusionSymptoms related to SDS are common in patients with NAFLD. The independent and interactive effects of intestinal bacteria and fungi might have collectively influenced the immune function and inflammation levels in NAFLD patients with SDS. These processes were likely associated with the intake of antioxidant and anti-inflammatory nutrients, as well as niacin.